GNIRS NIR Integral Field Spectroscopy of NGC 5128 - Díaz, R. J. (2021)
We present observations of the active nucleus of NGC 5128 obtained with the integral field unit (IFU) available at GNIRS spectrograph until 2007. This is the nearest AGN and is completely hidden to the optical range by a strong dust lane due to the edge-on orientation of the galaxy disk. The A'-band (1.9 — 2.55 μηι) IFU spectra uncovered the nuclear emission and allowed a new determination of the supermassive black hole mass, plus mapping the molecular gas with a spatial resolution of ~ 7 pc. This work allows us to explore the scientific potential of the integral field capabilities in GNIRS, considering that Gemini is upgrading the instrument with the addition of two IFUs working in the spectral range 0.9 — 5.4 μηι, which will be available by the end of 2021. One of the IFUs will operate under natural seeing, allowing a field of 3.2" x 4.8" sampled each 0.15" with a spectral resolution R ~ 7200. The other unit will complement Gemini North adaptive optics system, sampling each 0.05" a field of 1.25" x 1.8", with R ~ 18000, an unprecedented spectral resolution for this kind of NIR integral field spectroscopy facility.